ASSESSMENT OF WATER QUALITY IN SITU TLAJUNG HILIR USING POLLUTION INDEX AND SAPROBIC QUOTIENT APPROACHES - Shakira, Shakira; Istiana, Rita; Saputri, Dina Dyah (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Situ Tlajung Hilir is a natural lake in West Java, utilized by the local community to support livelihoods and contributing to the balance of the surrounding ecosystem. However, pollution from industrial and residential activities has raised concerns over its declining water quality. This study aims to assess the water quality of Situ Tlajung Hilir using the Pollution Index (PI) and Saprobic Quotient (SQ) methods. A descriptive quantitative approach with purposive sampling was conducted at four observation stations. Research activities included field observation, sample collection, measurement of physical, chemical, and biological parameters, and laboratory analysis. Instruments were calibrated prior to use. PI values ranged from 1.02 to 1.04, indicating a slightly polluted status based on the Decree of the Minister of Environment No. 115 of 2003. SQ values ranged from -0.10 to -0.79, reflecting moderate to fairly heavy pollution. The PI analysis showed that dissolved oxygen (DO) and temperature did not meet Class III water quality standards. SQ analysis revealed a dominance of Euglenophyceae and Paramecium (Ciliates), both indicators of organic pollution. In conclusion, the water quality of Situ Tlajung Hilir is categorized as slightly to fairly heavily polluted. Emphasizing the need for ongoing monitoring and improved waste management to protect the aquatic ecosystem.